2014
DOI: 10.1002/ca.22457
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the architecture of the vastus medialis oblique muscle in athletic and sedentary individuals: An in vivo ultrasound study

Abstract: There is thought to be a relationship between the vastus medialis oblique muscle (VMO) and patellofemoral pain syndrome (PFPS), a condition that has a high prevalence in young athletic individuals. Following a suggestion that there may be a link between the architecture of the VMO and an individual's activity level, the aim of this study was to determine any differences in two measurable parameters of the VMO between two populations with widely differing activity levels. The parameters measured were VMO fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
2
16
1
Order By: Relevance
“…A study by Benjafield et al, [29] found an average insertion ratio of 43.0% in athletic individuals, compared to 39.5% in sedentary individuals (the overall initial ratio in our study was 36.83%, which supports the low Tegner scores reported by the participants). The increase in insertion length, and hence increased ratio, following the exercise programme, enables a greater medial pull on the patella by the VMO, facilitating doi: 10.7243/2055-2386-4-3 correction of the lateral tilt and shift often seen in PFPS.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A study by Benjafield et al, [29] found an average insertion ratio of 43.0% in athletic individuals, compared to 39.5% in sedentary individuals (the overall initial ratio in our study was 36.83%, which supports the low Tegner scores reported by the participants). The increase in insertion length, and hence increased ratio, following the exercise programme, enables a greater medial pull on the patella by the VMO, facilitating doi: 10.7243/2055-2386-4-3 correction of the lateral tilt and shift often seen in PFPS.…”
Section: Discussionsupporting
confidence: 86%
“…The ultrasound technique used in this study followed the method that has been validated and described in several previous studies [18,[25][26][27][28][29]. Participants were positioned supine on the examination couch; a pillow was placed under the ankles to immobilise the lower limbs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However data from asymptomatic in vivo investigations are limited. A study by Benjafield et al () on subject groups with differing activity levels found an average VMO fiber angle of 67.8° for athletic groups (Tegner score > 7), and 53.6° for sedentary groups (Tegner score < 3). The average VMO fiber angle of 62.24° reported here before exercise is within the expected range as the study was limited to subjects with a Tegner score of 5 or less.…”
Section: Discussionmentioning
confidence: 98%
“…Three measurements were recorded in each procedure: patella length, insertion length and VMO fiber angle. The methodology used here follows previous studies in which the ultrasound technique has been shown to be statistically robust and accurate (Lin et al, ; Jan et al, , Engelina et al, ; Engelina et al, , Benjafield et al, ).…”
Section: Methodsmentioning
confidence: 99%